Effect of medium or high concentrations of in-office dental bleaching gel on the human pulp response in the mandibular incisors - Roderjan, Douglas Augusto; Stanislawczuk, Rodrigo; Soares, Diana Gabriela; de Souza Costa, Carlos Alberto [UNESP]; Favoreto, Michael Willian; Reis, Alessandra; Loguercio, Alessandro D. (Korean Academy of Conservative Dentistry, 2023)
Objectives: The present study evaluated the pulp response of human mandibular incisors subjected to in-office dental bleaching using gels with medium or high concentrations of hydrogen peroxide (HP). Materials and Methods: The following groups were compared: 35% HP (HP35; n = 5) or 20% HP (HP20; n = 4). In the control group (CONT; n = 2), no dental bleaching was performed. The color change (CC) was registered at baseline and after 2 days using the Vita Classical shade guide. Tooth sensitivity (TS) was also recorded for 2 days post-bleaching. The teeth were extracted 2 days after the clinical procedure and subjected to histological analysis. The CC and overall scores for histological evaluation were evaluated by the Kruskal-Wallis and Mann-Whitney tests. The percentage of patients with TS was evaluated by the Fisher exact test (α = 0.05). Results: The CC and TS of the HP35 group were significantly higher than those of the CONT group (p < 0.05) and the HP20 group showed an intermediate response, without significant differences from either the HP35 or CONT group (p > 0.05). In both experimental groups, the coronal pulp tissue exhibited partial necrosis associated with tertiary dentin deposition. Overall, the subjacent pulp tissue exhibited a mild inflammatory response. Conclusions: In-office bleaching therapies using bleaching gels with 20% or 35% HP caused similar pulp damage to the mandibular incisors, characterized by partial necrosis, tertiary dentin deposition, and mild inflammation.
Keywords: Hydrogen peroxide; In-office bleaching; Odontoblasts